Development and validation of a fast quantitative real-time PCR assay for the detection of African swine fever virus - Hwang, Hyun Jin; Choi, Yun Seong; Song, Kyungyoung; Frant, Maciej; Kim, Jeong Hee (Frontiers in Veterinary Science, 2023)
African swine fever virus (ASFV) is a double-stranded DNA virus that causes African swine fever (ASF), a lethal hemorrhagic fever that is highly contagious among domestic pigs and wild boars. Due to the high mortality rates and highly contagious nature of the ASF, it is important to develop a fast detection method for ASFV with high sensitivity and specificity to take an immediate action to stop wide spread of the virulent disease. Therefore, a fast and quantitative molecular detection method of ASFV is presented in this study. A total of 24 genotypes of ASFV have been identified based on nucleic acid sequences of the major capsid protein p72. The primers and probe of the present assay was designed to detect all of the p72-based genotypes of ASFV. The turnaround time for PCR detection was within 50 min which is at least about two-times faster compared to other PCR assays. Limit of detection (LoD) was 6.91 genomic copies/reaction for the most virulent genotype II. LoD values for other genotypes were within 10–20 copies/reaction. Cross-reactivity of the assay was validated using a panel of pathogens related to swine disease, and no cross-reactivity was observed. Positive and negative clinical samples (50 samples each) obtained from sick and healthy animals, were used to validate the assay. The results showed that 100% agreement for both positive and negative samples. In summary, the assay described in this study offers the advantage of rapid detection of all genotypes of ASFV with high sensitivity and specificity. The assay is a valuable tool both in clinical and laboratory uses for sensitive and fast detection of ASFV.